Flow of SWCNT and MWCNT based hybrid nanofluids in a semi-circular enclosure with corrugated wall - Sohail Nadeem; Ayesha Siddiqua; Jehad Alzabut (Advances in Mechanical Engineering)
Heat transfer mechanisms participate to fulfill the necessities of modern technologies. The phenomenon of heat transport has implementations in multiple fields including metal working, heating systems, thermal management in spacecraft, solar energy, and automobile engines. In the current novel work, heat transfer mechanism in a semi-circular enclosure with corrugated circular wall is studied numerically. A hybrid nanofluid consisting of water as the base fluid and solid particles of single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) is considered. Prevailing mathematical equations are explained by finite element method with the help of COMSOL Multiphysics. The study examines various volume fractions of solid particles over a broad range. The SWCNT volume fraction is adjusted from 0.02% to 0.1%, while the MWCNT volume fraction ranged from 0.01% to 0.04%. Velocity, temperature, and pressure contours are imagined. Local and average Nusselt numbers are studied for each of the cases. The results indicate that heat transfer in the semi-circular enclosure improves with higher volume fractions of solid particles. As the volume fraction of solid particles increases, the average Nusselt number over the heated surface decreases.